1000 wajah Pram dalam kata dan sketsa - Toer, Pramoedya Ananta (Lentera Dipantara, 2009)
Responses and praises on Pramoedya Ananta Toer's literary works; festschrift in honor of his 1000th death anniversary
Keywords: Toer; Pramoedya Ananta / 1925-2006 / Appreciation; Aufsatzsammlung